Studi Kitab ‘Ilm Ṭabaqāt Al Muḥadditsīn Karya As’ad Sālim Tayyim - Hanief Monady (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2016)
Hadith sciences has many branches of subject, including rijāl al-ḥadīts, al-jarḥ wa al-ta’dīl, al-nāsikh wa al-mansūkh, and much more. An attempt to explain these branches of Hadith sciences needs to be continued. One of the representative work in this field is the book entitled ‘Ilm al-Ṭabaqāt al-Muḥadditsīn, written by As’ad Salim Tayyim. This book discusses one of the of ‘Ulūm al-Ḥadīth branches, namely’ ‘Ilm al-Ṭabaqāt. In this book, As’ad Salim Tayyim gives maximum effort in explaining this branch by way of brief, concise, and clear. This article tries to explain the detailed parts of the book. It facilitates the reader in understanding the contents of the book and also gives some information about one of ‘Ulūm al-Ḥadīth discourse.[Ilmu Hadis yang memiliki banyak cabang ilmu, diantaranya adalah rijāl al-ḥadīts al-jarḥ wa al-ta’dīl, al-nāsikh wa al-mansūkh, dan masih banyak lagi. Oleh sebab itu usaha untuk menjelaskan Ilmu Hadis atau cabangnya masih harus terus dilakukan. Salah satu buah jerih payah tersebut adalah kitab dengan judul ‘Ilm al-Ṭabaqāt al-Muḥadditsīn yang ditulis oleh As’ad Sālim Tayyim. Kitab ini adalah kitab yang membahas mengenai salah satu cabang dari ‘Ulūm al-Ḥadīth, yaitu ‘‘Ilm al-Ṭabaqāt. Dalam kitab ini, As’ad Sālim Tayyim memberikan usahanya semaksimal mungkin dalam menjelaskan ilmu tersebut dengan cara ringkas, padat, dan jelas. Tulisan ini berusaha untuk memaparkan apa yang ada dalam kitab tersebut secara terperinci. Hal ini untuk memudahkan para pembaca dalam memahami isi kitab tersebut untuk menambah informasi terkait salah satu wacana ‘Ulūm al-Ḥadīts.]